THE ROLE OF INDUSTRIAL ENTERPRISES IN THE DEVELOPMENT OF THE NATIONAL ECONOMY (Conference Zone, 2022)
This article discusses some issues such as increasing the role of industrial enterprises in the development of the national economy as key factors in the formation of its components